Using environmental DNA method to clarify the distribution of Pampus echinogaster in the East China Sea - Zhang, Haobo; Li, Yuan; Zhong, Lanping; Gao, Tianxiang; Wang, Xiaoyan (Frontiers in Marine Science, 2022)
Environmental DNA (eDNA) is becoming a potentially valuable survey technique to monitor marine organisms, especially when the research spans wide-ranging temporal or spatial dimensions. Pampus echinogaster plays an important role in China's marine fisheries. However, the stock of P. echinogaster is gradually declining, so the fishery protection and management of P. echinogaster are becoming crucial. To achieve the non-invasive and large-scale monitoring of P. echinogaster, we developed a specific quantitative real-time PCR (qPCR) method based on eDNA technology. Results showed that positive signals of P. echinogaster eDNA were successfully detected at 36 sites (82% of the total) in the East China Sea. Significant differences in eDNA concentrations between the southern and northern stations in the East China Sea suggested differences between the life histories of P. echinogaster in these two sea areas. The hotspot was found around the central areas of the East China Sea, especially around the Taizhou seawater (Jiaojiang Estuary). Vertical distribution showed that the eDNA hotspots were primarily concentrated in the middle and upper layers (0–40 m). The distribution results of eDNA hotspots were similar to those of previous findings through motor–trawl capture, indicating the validity of the eDNA results. The relationship between environmental factors and the eDNA concentration showed that PO43- was significantly correlated with the P. echinogaster eDNA concentration. Overall, our study indicated that the eDNA approach was an effective survey method and can be used as a monitoring tool. We advocate this monitoring approach to guide the management and conservation of large-scale sea areas and thus enable their initially surveying to provide the best information about species-specific distribution.